Analysis of Factors that Influence the Customer Loyalty in Modern Pharmacy Retail in Indonesia - Tandiono, Josephine; Agus, Anna Amalyah (Fakultas Ekonomi Universitas Samudra, 2024)
The study analyzes several factors that are seen to influence the customers loyalty in modern pharmacy retail. This study was conducted at Watsons Indonesia. This study examines the influence of in-store experience (IE), membership programs (M), and use of private labels (PL) on customer loyalty. Shopping habits are proposed as a variable that moderates the three independent variables on customer loyalty. Data was collected from a sample of 232 Watsons Indonesia customers and the relationship between variables was tested using structural equation models. The findings show that IE and M are not proven to have a significant influence, but PL is proven to have a significant influence on customer loyalty at Watsons Indonesia. Furthermore, shopping habits do not significantly moderate EI, PL, and M in building customer loyalty of the company.